Discursos sobre a temática do abuso sexual de crianças e da pedofilia na mídia escrita - Moraes, Julianne Caju de Oliveira Souza (2017)
This masters’ thesis was developed within the Master Degree Program in Education of the Federal University of Mato Grosso, in Rondonópolis city, in the line of research Language, culture and knowledge construction process. It was composed within the Study Group Childhood, Youth and Contemporary Culture (GEIJC, Grupo de Estudos Infância e Juventude na Cultura Contemporânea). This research aims to analyze the emergence of articles in printed media on the subject of pedophilia and sexual abuse against children and adolescents, thus cooperating in the discussions on the rights of the childhood and adolescent and the social developement of Brazilian childhood and youth. Since the decade of 1990, pedophilia and sexual abuse against children and adolescents are significant issues that claim great attention from Brazilian society. In fact, these are issues that need to be addressed promptly. To do so, understanding the outline of their social definition, that is, the way these issues are viewed by society has repercussions on the way in which they are intended to face it. In the wake of this thought, considering the media as an important social actor in the interpretation of social issues, we seek to identify the publicization, as well as rhetoric and discursive repertoires, used in the emergence of the themes of sexual abuse against children and adolescents and pedophilia. This study enquires whether the substantial increasing of these themes, in the last two decades, has been contributed to the confrontation of these problems in Brazilian society or if the dramas around these issues have been used to feed a sensationalist approach to this subject. This research was developed within J.B. Thompson’s methodological proposals called Depth Hermeneutics (DH). We’ve analyzed the newspaper Folha de São Paulo’s two-hundred and twenty-one articles on the subject of pedophilia and “child sexual abuse”, in the period of 1976 and 1990. The data analyzed indicated pedophilia had been ignored by Folha de São Paulo until the 80’s, as from the 90’s have been the object of increasing attention. Also, it shows that the publicization is associated to the emergence of sexual violence against children and teenagers, in the international scenario, and also to the diffusion of children and adolescents’ rights, in the Brazilian scenario, thanks to the promulgation of the Children and Teenager Statute (ECA, Estatuto da Criança e do Adolescente) in 1990. We also notice that the newspaper uses the expression pedophilia to refer to “child sexual abuse”, and that this choice causes more impact on the audience, being quite sensationalist. Thus, the term pedophilia was being built up, meaning that all and any sexual abuse against children and adolescents has correlation with pedophilia. More than that, it became a major social problem and, as it was written began to cause panic among the public. However, this characterization does not work as sensationalism only, but it has deleterious effects in facing this issue, as it also contributes to build a conception of abuser as a sick person, defocusing the character of “child sexual abuse” as a cultural phenomenon produced and sustained by a society structured on age and gender inequalities and sustained by patriarchal values and practices.